The Implementation of RPG Concept on Breakout Games Using LibGDX Framework - Andres Nodas; Djajasukma Tjahjadi; Ali Rahman (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2021)
As technology becomes more global, RPG games runs into a good development. One of which is a combination of RPG with another games. This journal aims to combine the breakout games and the RPG which has its characteristics. This game development uses prototyping method, in which analysing the necessity and determining the goals of the software. Then, prototype will be created and evaluated regularly so that the result can use 2D graphics. This game also can be used as a reference to reflexes practising. A modeling is conducted to design ‘use case,’ scenario process, activity diagram, class diagram, and sequence diagram as well as to conduct an interface design. A calibration that is used, is calibrating the programme which is created as well as the features in the programme itself. It can be concluded that the construction of RPG games combination and breakout using eclipse and libgdx works well. In addition, it uses the components such as TMX tile map, sprite, sprite batching, box2d and input handling.